Utilising causal loop diagram to explore public integrity for effective COVID-19 preventive measures in Malaysia - Cheng, Jack Kie; Muhamad Tamyez, Puteri Fadzline; Mohamad, Fazeeda; Zetty Ain, Kamaruzzaman; Zulkipli, Faridah; Mohd Zainudin, Maizura (Universiti Malaysia Pahang, 2022)
COVID-19 creates an unprecedented crisis in our lifetimes. The escalating rates of COVID-19 infection brings calamity to many parts of the world. Malaysia has been in a fierce battle with COVID-19 since March 2020 but the endgame is still obscure. Since the beginning of the pandemic, many preventive measures are implemented by the Malaysian government. Some of the strategies such as lockdown and movement restrictions are effective in flattening the curve of COVID-19. However, over a period of time, negative unintended consequences such as pandemic fatigue emerged due to prolong confinement. Lockdown is also an expensive measure that impacts the community livelihood and subsequently risking Malaysia’s economy. After two years of the pandemic, with the success of COVID-19 vaccination programme, Malaysia may be ready to return to normalcy. However, the world is alarmed with new deadly COVID-19 variant which puts Malaysia in constant risk of resurge of cases. This paper aims to understand how implemented preventive measures interacted with each other and collectively influence the spread of COVID-19 in Malaysia. Only by understanding these interaction, more effective, economical and sustainable counter measures that safe lives without compromising people livelihood can be introduced. The causal loop diagram, an essence of system dynamics is developed to capture these interconnections and provide meaningful insights. The role of community and public integrity are also observed in this study.